ARTICULATION OF DISCOURSE IN FAMILY COMMUNICATION: AN ANALYSIS OF MARITAL DISHARMONY FROM THE PERSPECTIVE OF LACLAU AND MOUFFE - Ni Luh Manik Puja Dewi (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Marital disharmony often occurs when inconsistencies emerge between words and actions within intimate relationships. Such tension reflects not only a failure in communication but also a deeper struggle over meaning shaped by social and cultural structures. This study examines how discursive articulations within family communication construct and influence marital disharmony through the theoretical framework of Ernesto Laclau and Chantal Mouffe. Employing a qualitative approach and critical discourse analysis, the research analyzes anonymized online news reports of domestic conflicts in Bali. The findings reveal that disharmony frequently arises from the intersection of traditional discourses emphasizing obedience, hierarchy, and patriarchal values with modern discourses promoting equality, openness, and emotional reciprocity. Hegemonic meanings such as the “ideal obedient wife” and “husband as family head” remain culturally dominant but are increasingly contested by more egalitarian interpretations. This study argues that disharmony should not merely be regarded as a relational breakdown but as a discursive moment that allows families to renegotiate the meanings of love, responsibility, and harmony within the dynamics of contemporary Balinese culture.